SULTAN GROUND: STUDI POLITIK HUKUM DAN HUKUM AGRARIA NASIONAL - Darmawan, Antonius Teddy; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
Business in the Special Region of Yogyakarta develops independently and has the characteristics of each region, this is shown by the fact that it has 5 (five) additional authorities from the Central Government. These powers include how positions are placed, duties, and responsibilities of governors and deputy governors, government institutional, cultural, land, and spatial planning authorities, and additional authority in the land sector. Based on Law No. 13 of 2012 concerning the Privileges of Yogyakarta and Government Regulation No. 10 of 1961 concerning Land Registration as a further implementation of article 19 of the UUPA, the Special Region of Yogyakarta has the privilege to regulate and manage the Royal Land, also known as Tanah Sultan (Sultan Ground) and Tanah Pakualaman (Pakualaman Ground). This regulation must be analyzed juridically in relation to the Land Law. The normative legal methods used include historical analysis of the arrangement of the Sultan's Land from the pre-colonial period to the independence era, as well as an analysis of the Laws and Regulations regarding the regulation of Sultan Land (Sultan Ground) with the National Land Law. The results of the methods and approaches used show that the Sultan of Yogyakarta has a domain over Sultan Ground land that is different from the State land.Keywords: Yogyakarta; Sultan Ground; Agrarian Law